The role of DDX19 and NUP214 in enterovirus 71 replication - Yang, Yuzhou (2015)
Enterovirus 71 (EV71) was identified as one of the major causative agent for Hand Foot and Mouth Disease (HFMD) which is increasing in occurrence and severity across the world, especially in the Asia-Pacific region. There are currently no treatments or vaccinations for HFMD. EV71 infection can lead to severe complications including acute flaccid paralysis, meningitis and encephalitis. As observed in recent outbreaks across different countries, enterovirus infection in children is a serious problem worldwide. As obligate parasites, viruses are able to exploit the functions of host factors for their own replication, making host factors attractive targets for therapeutic intervention. Previous research identified two host factor proteins, DDX19 and NUP214, which interact with EV71 and are possibly involved in EV71 viral replication. With existing publications illustrating the role of DDX19 and NUP214 in cellular nuclear export and mRNP remodeling, this study aims to confirm these mechanism of action of the two host factors in EV71 replication.